STUDI PERBANDINGAN KEMAMPUAN MEMBACA AL-QUR’AN METODE TILAWATI DENGAN METODE UMMI - Magfiroh, Ismi; Khalfiah , Yuliani; Afifah , Neela (STAI Ma'had Aly Al-Hikam Malang, 2024)
ABSTRACT Following up on previous research which stated that the Tilawati and Ummi methods both had a positive impact on the development of students' Al-Qur'an reading. The aim of this research is to describe the ability to read the Al-Qur'an of santri using the Tilawati method at TPQ Nurul Furqan Palangka Raya, the ability to read the Al-Qur'an of santri using the Ummi method at RQ Al-Hijaz Palangka Raya. This research uses a quantitative method by comparing the results of the ability to read the Al-Qur'an using these two methods. The research instrument used was an oral test. The samples in this study were 10 students at TPQ Nurul Furqan and 10 students at RQ Al-Hijaz who were in the Al-Qur'an class. Data analysis uses the